Rosiglitazone Prevents High Glucose-Induced Vascular Endothelial Growth Factor and Collagen IV Expression in Cultured Mesangial Cells. (17th May 2009) - Whiteside, Catharine; Wang, Hong; Xia, Ling; Munk, Snezana; Goldberg, Howard J.; Fantus, I. George
Abstract : Peroxisome proliferator-activated receptor (PPARγ ), a ligand-dependent transcription factor, negatively modulates high glucose effects. We postulated that rosiglitazone (RSG), an activator of PPARγ prevents the upregulation of vascular endothelial growth factor (VEGF) and collagen IV by mesangial cells exposed to high glucose. Primary cultured rat mesangial cells were growth-arrested in 5.6 mM (NG) or 25 mM D-glucose (HG) for up to 48 hours. In HG, PPARγ mRNA and protein were reduced within 3 h, and enhanced ROS generation, expression ofp 22 phox, VEGF and collagen IV, and PKC-ζ membrane association were prevented by RSG. In NG, inhibition of PPARγ caused ROS generation and VEGF expression that were unchanged by RSG. Reduced AMP-activated protein kinase (AMPK) phosphorylation in HG was unchanged with RSG, and VEGF expression was unaffected by AMPK inhibition. Hence, PPARγ is a negative modulator of HG-induced signaling that acts through PKC-ζ but not AMPK and regulates VEGF and collagen IV expression by mesangial cells.